The relationship between parental stress, coping and depression among mothers of children with ADHD in the Klang valley - Mustafa, Qarem Mohamed (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
Research has shown that becoming a parent may come with its occasional stress, especially when parenting children with developmental disorders. One possible negative outcome due to high parental stress is an increase in depressive symptoms. However, the use of coping strategies could moderate the relationship between parental stress and depressive symptoms. This study examined the relationship between parental stress, coping, and depressive symptoms among mothers of children with attention-deficit hyperactivity disorder (ADHD) in which it was hypothesized that there is a significant interaction between the variables. By using purposive sampling technique, a total of 94 Malay mothers from Klang Valley, Malaysia, with a mean age of 39.67 were identified and participated in the study. This is a cross-sectional study in which the measures used were the Parental Stress Inventory-Short Form (PSI-SF), Brief-COPE, and Centre of Epidemiological Study-Depression (CES-D). The findings of this study showed a significant positive relationship between parental stress and depressive symptoms (β = .368, p < .001) and between age of the child with the use of problem focused coping (r = .277, p < .01). A significant negative relationship was found between problem focused coping and depressive symptoms (β = –.737, p < .001). However, both coping strategies (i.e., problem-focused and emotion-focused) were not significant moderators for the relationship between parental stress and depressive symptoms. The findings partially support the application of the Transactional Model of Stress on the population of mothers of children with ADHD. Practical implications of the findings were also discussed.